2016
DOI: 10.3390/ijerph13070715
|View full text |Cite
|
Sign up to set email alerts
|

Origin-Oriented Elemental Profile of Fine Ambient Particulate Matter in Central European Suburban Conditions

Abstract: Twenty-four-hour samples of fine ambient particulate matter (PM2.5; particles with aerodynamic diameters ≤2.5 µm) were collected in a suburban (quasi-rural) area in Racibórz (Poland) between 1 January 2011 and 26 December 2012. The samples were analyzed for the contents of 28 elements. Sources of PM2.5 were identified and the contribution of each source to the PM2.5 concentration was assessed using an enrichment factor (EF) analysis, a principal component analysis (PCA), and multi-linear regression analysis (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…The finest fraction of particulate matter may be present in the atmosphere for a long time; therefore, it may be transported a long distance [38]. Higher concentrations of particulate matter in the heating season in Poland are confirmed by numerous studies [29,39,40]. Studies carried out in Wrocław and Poznań confirmed that concentrations of all PM fractions are higher in the heating period than in the non-heating period.…”
Section: Analysis Of Variability In Concentration Of Particulate Mattmentioning
confidence: 82%
“…The finest fraction of particulate matter may be present in the atmosphere for a long time; therefore, it may be transported a long distance [38]. Higher concentrations of particulate matter in the heating season in Poland are confirmed by numerous studies [29,39,40]. Studies carried out in Wrocław and Poznań confirmed that concentrations of all PM fractions are higher in the heating period than in the non-heating period.…”
Section: Analysis Of Variability In Concentration Of Particulate Mattmentioning
confidence: 82%
“…The mean value of the mass concentration of PM 2.5 in the rural areas was at a similar level to the concentration of PM 2.5 determined not only in Opole (32.4 g/m 3 , p-value = 0.21), but also in the towns with the highest level of pollution in Poland. At the same time, these values considerably exceeded the mass concentrations measured in the rural areas in Central and Northern Europe [6]. A statistically insignificant difference (p-value = 0.38) was also noted during the comparison of mean mass concentrations of PM 10 Figs.…”
Section: Measurements Procedures and Results Analysismentioning
confidence: 62%
“…It's widely known, that in Poland, the air quality is worse during the cold season than in warm [6]. In the cold season, the main source of ambient aerosol is uncontrolled emission from local individual heating systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies confirm connection between the size of the surface area, and the ability of PM particles to cumulate metals and metalloids. In the Polish urban areas, approximately 70-90% of total PM-bound metal mass is bound to submicron particles (PM1) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%